Open-label, randomized, phase 3 study of coformulated favezelimab and pembrolizumab versus chemotherapy in patients with relapsed or refractory classical hodgkin lymphoma refractory to anti-PD-1 therapy: Keyform-008 - Lavie, David; Timmerman, John; Garcia-Sanz, Ramon; Kim, Won Seog; Kim, Tae Min; Avigdor, Abraham; Dierickx, Daan; Jagadeesh, Deepa; Molin, Daniel L.; Herrera, Alex F. (American Society of Hematology, 2023)
Background: The importance of PD-1 therapy in relapsed or refractory (R/R) classical Hodgkin Lymphoma (cHL) is well established, with PD-1 inhibitors such as pembrolizumab being a standard of care option for patients. However, most patients eventually develop progressive disease and optimal therapy after anti-PD-1 failure has not been determined. The inhibitory checkpoint receptor, lymphocyte-activation gene 3 (LAG-3) is expressed in cHL tumor microenvironments and upregulation of LAG-3 is considered to play an important role in anti-PD-1 resistance. Favezelimab (MK-4280) is a humanized immunoglobulin G4 antibody that binds to LAG-3 and blocks interaction with major histocompatibility complex Class II ligands. Results from the ongoing phase 1/2 MK-4280-003 study of the combination of favezelimab and pembrolizumab demonstrated manageable safety and promising antitumor activity in patients with anti-PD-1-refractory R/R cHL. The randomized, open-label, parallel group, active-controlled, phase 3 KEYFORM-008 study (NCT05508867) is designed to evaluate efficacy and safety of the coformulation of favezelimab and pembrolizumab versus physician's choice of chemotherapy in patients with anti-PD-1-refractory R/R cHL.
Keywords: Randomized; Coformulated Favezelimab; Anti-PD-1 Therapy